2013
DOI: 10.1177/0003319713502392
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial and Platelet Function in Children With Previous Kawasaki Disease

Abstract: We investigated whether children with a previous Kawasaki disease (KD) have evidence of abnormal vascular and/or platelet function. We included 14 patients with previous KD and 14 matched controls. We assessed endothelial function by flow-mediated dilation (FMD), carotid intima-media thickness (cIMT), coronary microvascular function by coronary blood flow response (CBFR) to cold pressor test, and platelet reactivity by measuring monocyte-platelet aggregates (MPAs) and CD41-platelet expression by flow cytometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…The causes and clinical implications of the persistent platelet activation after the acute stage in patients with KD were probably due to the persistence of subclinical low-grade inflammation in KD (21). A recent study reported that children with a previous episode of KD showed increased platelet activation when compared with healthy participants despite no apparent vascular abnormality at follow-up (22). …”
Section: Discussionmentioning
confidence: 99%
“…The causes and clinical implications of the persistent platelet activation after the acute stage in patients with KD were probably due to the persistence of subclinical low-grade inflammation in KD (21). A recent study reported that children with a previous episode of KD showed increased platelet activation when compared with healthy participants despite no apparent vascular abnormality at follow-up (22). …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a recent Dutch study noted a small increase in cIMT in participants with a history of KD regardless of the presence of aneurysms in the subacute phase . Only two studies focus exclusively on KD patients without coronary artery changes or with transient coronary artery dilatations and both have small sample sizes; neither detected any differences in cIMT compared to controls . Overall, irrespective of ethnicity, studies performed on average less than 10 years since acute KD are more likely to detect increased cIMT compared to controls, although data are inconsistent .…”
Section: Resultsmentioning
confidence: 92%
“…Three studies show no changes in FMD; 2 studies have less than 15 KD patients each . McCrindle et al found no difference in FMD in predominantly European patients with persistent coronary aneurysms despite metabolic and lipid abnormalities .…”
Section: Resultsmentioning
confidence: 99%
“…Two patients also received IV in iximab infusion (5 mg/kg)-one child with giant coronary artery aneurysm and the other with severe systemic disease and transient CAA. Antiplatelet dose of aspirin was continued for 3 months in one child as he persisted in having elevated platelet counts (640x10 9 No signi cant differences in MPA% were noted between patients with and without CAAs […”
Section: Resultsmentioning
confidence: 99%
“…Occurrence of coronary thrombosis and premature arteriosclerosis in KD suggests that excess activation of platelets and coronary vasculitis may play an important role in progression of vascular damage in KD. Though platelet activation has been studied in KD, there is paucity of literature on ow cytometry-based assessment of leukocyte-platelet aggregates in KD and there are no data from developing countries (7)(8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%